Distillation Column: Review of Major Disturbances - Ammar Taqvi, S.A. (Institute of Electrical and Electronics Engineers Inc., 2019)
The continuous increase in the global energy demand obliges the necessity of energy production and its efficient utilization. The energy conservation is a primary concern of every process industry due to the increasing fuel prices. The distillation column is considered as one of the essential energy-intensive unit operations of any chemical and process industry. Therefore, process engineers are finding ways for efficient process monitoring and better control. However, the non-productive nature and the complexities in the column has increased the difficulties to handle this unit operation. Hence, it is desirable to operate the column efficiently to attain high product quality. The energy consumptions during distillation can have a substantial impact on overall profitability. A critical review of the various disturbances and operational difficulties has been presented. The causes, consequences and recommendation to handles various anomalies in distillation has also been presented which may help to identify the root cause while doing detection and diagnosis of various faults. Â© 2019 IEEE.